1970
DOI: 10.1038/bjc.1970.19
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Carcinomas in the Nasal Cavity of Rats by Dioxane

Abstract: SUMMARY.-Six out of 120 rats fed dioxane in drinking water at levels of 0 75, 1.0, 1-4 or 1.8% developed carcinomas in the nasal cavity. Spontaneous tumors at this tissue localization have not been reported to occur in laboratory animals. The carcinomas were pre-eminently of epidermoid type with few adenocarcinomatous areas and epithelial papillomas. Four rats with carcinoma of the nasal cavity had hepatocellular carcinoma in addition.SPONTANEOUS tumors of the nasal cavity of laboratory animals have so far not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

1973
1973
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 11 publications
(6 reference statements)
0
21
0
2
Order By: Relevance
“…The overt toxic effects of dioxane include hepatocellular and renal tubular epithelial cell degeneration and necrosis (Kociba 1975). Dioxane-induced nasal and hepatic tumors were reported in studi~ in which Wistar or CD rats were administered from 0.75 to 1.8% dioxane in the drinking water for 13 months (Argus et al 1965(Argus et al , 1973Hoch-Ligeti et al 1970). These same tumor types were seen in the high dose group only of Sherman rats exposed to 0.01, 0.1, and 1% dioxane in the drinking water for 2 years ).…”
Section: Introductionmentioning
confidence: 92%
“…The overt toxic effects of dioxane include hepatocellular and renal tubular epithelial cell degeneration and necrosis (Kociba 1975). Dioxane-induced nasal and hepatic tumors were reported in studi~ in which Wistar or CD rats were administered from 0.75 to 1.8% dioxane in the drinking water for 13 months (Argus et al 1965(Argus et al , 1973Hoch-Ligeti et al 1970). These same tumor types were seen in the high dose group only of Sherman rats exposed to 0.01, 0.1, and 1% dioxane in the drinking water for 2 years ).…”
Section: Introductionmentioning
confidence: 92%
“…There is evidence that long-term oral administration of 1,4-dioxane causes hepatic and nasal cavity tumors in rodents, [8][9][10][11][12] and accordingly the IARC has classified 1,4-dioxane as a group 2B carcino- gen. 6) With regard to a cancer endpoint, a total daily intake (TDI) of 16 µg of 1,4-dioxane/kg body weight/ day has been calculated by applying an uncertainty factor of 1000 that incorporates 100 for inter-and intraspecies variation and 10 for nongenotoxic carcinogenicity to the no observed adverse effect level of 16 µg/kg body weight/day, as found in a longterm study involving drinking water in rats. 14,15) The 0.440 µg intake of 1,4-dioxane we measured in our study corresponds to 0.055% of the calculated TDI (0.440 µg/{16 µg/kg body weight/day × 50 kg}).…”
Section: Risk From 14-dioxane In Foodmentioning
confidence: 99%
“…6) Long-term oral administration of 1,4-dioxane has been shown to cause tumors in the liver and gallbladder in guinea pigs, 7) and in the nasal cavity and liver of rats. [8][9][10][11] 1,4-Dioxane has also demonstrated promoter activity in studies in mice using a two-stage carcinogenic test. 12) Levels of 1,4-dioxane between 0.2 mg/l and 1.5 mg/l were also detected in tap water samples collected during 1995 and 1996 from six cities in Kanagawa prefecture, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…As the DMBA and croton oil responded as expected in terms of skin tumor promotion. The extent and variety of the lesions produced by DMBA and dioxane were unexpected, however, previous studies have shown dioxane to be a hepatocarcinogen (9) and to induce carcinomas in the nasal cavity of rats receiving dioxane in drinking water (10).…”
Section: Discussionmentioning
confidence: 94%